Profil Antropometri Atlet Elit Dayung Puteri Indonesia - Tafaqur, Muhamad; Yusup, Ucup; Kusdinar, Yopi; Nurjaya, Dede Rohmat (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2023)
Rowing athletes' anthropometry is one of the factors that influences performance in rowing. The aim of this research is to determine the anthropometric profile of Indonesian women's rowing athletes in the 2023 rowing numbers. The research method used in this research is a descriptive method. The instruments used are anthropometric tests using a height measuring device (microtoise), a weight measuring device (digital scales with an accuracy of 0.1 kg), and a skinfold caliper. The sample in this study was 4 Indonesian female rowing elite athletes in 2023. The sampling technique uses total sampling. The results of the research show that the average height of Indonesian elite female rowing athletes in 2023 in rowing is 171.8 cm, the average body weight is 63 kg, and the average body mass index is 21.32 kg/m2. The Body Mass Index (BMI) of Indonesia's elite female rowing athletes in 2023 rowing numbers are all in the normal category. The body fat percentage of one elite Indonesian female rowing athlete in 2023 rowing numbers is in the ideal category and three athletes are in the excessive category. It is hoped that the results of this research can be a reflection for both coaches and athletes in efforts to improve the performance of female rowing athletes in accordance with the expected targets.